Processo administrativo eletrônico - plano de implantação na Controladoria Geral do Estado de Goiás - Moraes, Fausto Cruzeiro de (2016)
This work has as a central issue the discussion of the administrative process in public organizations and proposes a model of plan of implementation the electronic process in the Comptroller General agency of the State of Goiás. The concern with the formal record of the grounds, opinions and actions of administrative acts public, materialized in administrative proceedings, leads to large volumes of paper documents, generated and handled daily, presenting challenges in transport, accommodation, storage and retrieval of these documents. Through analysis of volumes, times and expenses involving the physical administrative processes of the state of Goiás and the General of the State of Goiás Comptroller, and with the support of a modeling and process simulation tool, it became clear how the electronic administrative process can contribute to reducing paper costs and greater speed in the processing of the administrative process. Added to this, the electronic process, based on computerized system can provide administrators greater management of the processes with greater control of the status and terms related thereto, as well as contributes to increased organ transparency. This study aimed to identify how the current administrative process based on paper, can be converted to electronic through the presentation of a deployment plan for the electronic administrative procedure before the General Comptroller of the State of Goiás (GO-CGE). For making the diagnosis, it was used the documentary analysis of the corporate database of administrative procedures, provided by the Protocol of Electronic System (SEPNET) of the State of Goiás. The results indicated reduction opportunity in the processing time of the administrative procedures up to 72,5 % of total time in the state of Goiás and average reduction of up to 149 calendar days in processing times in CGE-GO. Moreover, the savings in paper volume in the state of Goiás can reach up to 10 million pages in administrative processes annually. In the case of CGE-GO, it was found possible to reduce the printing costs between R$ 5,420.28 and R$ 25,552.77 per year. Was also identified potential gains for the service of Public Transparency, offering greater publicity of the processes. This work generated as product the deployment plan model the electronic administrative process, which is one of the requirements needed for acquiring for free of the electronic process software that has been adopted by the Federal Government of Brazil.